Platinum doped titanium dioxide nanocomposite an efficient platform as anode material for methanol oxidation - Shahid, Mehmood (Elsevier, 2021)
TiO2@Pt nanocomposite was synthesized using a simple one-step coprecipitation method as an electrocatalyst for methanol oxidation. Pt nanoparticles were supported by using TiO2 as a support material, thereby providing strong metal-support interactions. The TiO2@Pt nanocomposite characterized by Field Emission Scanning Electron Microscope (FESEM) and Energy Dispersive X-ray analysis (EDX) revealed the spherical shape of TiO2 crystalline matrix with finely dispersed Pt nanoparticles. In the powder X-ray diffraction (XRD) analysis, the diffraction peaks observed for the TiO2 and TiO2@Pt nanocomposites were composed of mixed phases of anatase and rutile. Electrochemical performances are evaluated in an aqueous 0.1 M KOH electrolyte and 0.1 M CH3OH as a target analyte. The Pt@TiO2 nanocomposite showed high electrocatalytic activity towards methanol oxidation, the results indicated that the bare Pt electrode has catalyzed the oxidation of methanol with a strongly weak oxidation peak (J 1/4 0.25 mA/cm(2)), while TiO2 modified Pt electrode which showed higher catalytic activity towards methanol oxidation with a current density of 0.48 mA/cm(2). The methanol oxidation was increased compared to a commercially available Pt/C reference catalyst, as shown by a shifted methanol oxidation peak potential and an increased peak current density. As demonstrated by cyclic voltammetry, these increased activities have been clarified by enhanced methanol oxidation activities. An enhanced methanol oxidation activity is attributed to the metal support interaction due to TiO2 nanoparticles, therefore resulting in a weak CO chemisorption on the surface of Pt. Finally, with such valuable features of electrochemical sensitivity and great catalytic activity, the synthesized TiO2@Pt-3 nanocomposite is used as the anode material for methanol fuel cell application. (c) 2021 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).